PENYULUHAN LITERASI KEUANGAN DAN DIGITALISASI BISNIS DI SMK YADIKA KOTA LUBUKLINGGAU - Miki Indika; Winata Nugraha; Riswanda Imawan Lingga; Rian Oktavianie; Anggia Syafitri; Suharto; Herawati; Subianto; Kusnadi Yudha Wiguna; Yayuk Marliza (Jurnal Masda, 2023)
This Community Service Program is carried out by lecturers of the Accounting Study Program and Digital Business Study Program, Faculty of Economics and Business, Musi Rawas University, which also involve students in order to provide insight and additional knowledge to Yadika Vocational School students, Lubuklinggau City regarding strategies for managing finances and dealing with technological developments . The method used is using lectures, power points with visual media and question and answer. The enthusiasm of the participants in participating in this counseling activity is a benchmark for the success of the Community Service agenda. This is shown by the interaction between the speakers and the participants in the question and answer session so that the discussion of the material gets deeper.